Role of free oxygen radicals in noise-related hearing impairment - Kaygusuz, I; Öztürk, A; Üstündag, B; Yalçin, S (Elsevier Science Bv, 2001)
This. study was aimed at defining the relationship between noise-related hearing impairment in industrial workers exposed to continuous noise. For this malondialdehyde and glutathione peroxidase were analyzed as free radical form and antioxidant form. A total of 60 patients working in the units of a hydroelectric power plant were included in the study. This experimental group was further divided into three subgroups of 20 workers, each group exposed to a different noise level. The control group consisted of 20 male volunteers employed in the Medical Centre where the study was carried out. A standard ascending/descending method was applied to the subjects of the experimental and the control groups in order to determine their hearing thresholds at seven different frequencies between 250 and 8000 Hz. Then, 10 ml blood was collected from each person to measure the malondialdehyde values in plasma and glutathione peroxidase activity in erythrocytes. Slight sensorineural hearing impairment was found in group I beginning at 4 kHz and in group II beginning at 6 kHz. Statistically significant differences were observed in group I and II when compared to the control group (P < 0.05). It was found that malondialdehyde levels increased in the experimental groups more than in the control groups. However, this increase was only significant in group I (P < 0.05). Erythrocyte glutathione peroxidase activity significantly increased in group I and II compared to the other groups (P < 0.05), also, the difference was significant between group I and II (P < 0.05). Accordingly, it is suggested that free oxygen radicals may take a role in noise-related hearing impairment. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: hearing impairment; noise; free oxygen radicals scavenging; antioxidant